Eruption cyst in a 2 y.o. patient located in the region of upper first deciduous molar - Piotr Osica; Karolina Osica; Cezary Hejduk; Anna Janas-Naze (Kazimierz Wielki University, 2018)
The article presents a case of a 2 year-old patient with a long lasting eruption cyst located in the region of tooth 54.